ANALISA KUALITAS AIR MINUM ISI ULANG DI KOTA PEKANBARU - Erik Nelson (Program Pascasarjana Universitas Riau, 2008)
The level of human healthy had influenced by many factor, one of them is environmental factor. Many effort toincrease the environmental healthy such as gets the control to quality of drink water. To get the healt water as astandard of water quality, so the water had processed, first, before consumpted. The process usually had bywater refill depot which find in many locations and used by people cause get low price. The result of thisresearch showed that material water quality, except from sources, it had required in bacteriologily. Thebacteriologic quality of water had drawed from each depot, it had fluctuated or inconsistent in requirements ofbacteriologic quality. In water products form each depot where analyzedmemenuhi syarat bakteriologis. Kualitas bakteriologis air minum yang dihasilkan pada tiap depot adalahberfluktuasi atau dengan kata lain tidak konsisten memenuhi persyaratan kualitas bakteriologis. Dalam produkair minum dari semua depot yang diteliti, terdapat kadar zat kimia ; arsen yang melampaui standar kesehatan.Sementara itu kadar zat kimia ; kadmium, selenium dan sianida yang melebihi standar kesehatan ditemukandalam poduk air minum pada 3 ( tiga ) depot dari 5 ( lima ) depot yang diteliti.